The Analysis of Self-Assessment Effect on EFL Students’ Speaking Performance - Sintayani, Ni Luh; Adnyayanti, Ni Luh Putu Era (Journal of Educational Study, 2022)
Studies indicated that EFL students were often struggling in speaking due to their fear of making mistake. This becomes a problem as speaking is an essential skill needed to be able to communicate in the target language and become successful learners. This study was conducted with the aim of investigating the effect of self-assessment on EFL students’ speaking performance.  It used library research with a method of document analysis by analyzing previous related studies and theories. The results indicated that self-assessment has positive effect on students’ speaking performance as it involves students in the process of evaluating their learning process, product or performance, and progress. The effects include identification of strengths and weaknesses, improvement of self-efficacy, and improvement of speaking performance. However, self-assessment needs to be implemented well by considering the assessment criteria and practices in order to achieve these positive effects.